Los hábitos de estudio y su incidencia en el rendimiento académico de los estudiantes de 10mo año de básica de la unidad educativa San Benildo La Salle.realizado por: Srta. Rosario del Carmen Novillo Zárate Srta. Lucia Ivonne Manzaba Márquez - Novillo Zárate, Rosario del Carmen (2015)
The study habits lead to develop the learning capacity of students to ensure success in homework. Although this habit begins to settle in school age, ideally from small get used to accomplish a task for a while, to go training this kind of study habits……